2020
DOI: 10.17097/ataunizfd.768620
|View full text |Cite
|
Sign up to set email alerts
|

Trabzon İline Ait Bazı Yerel Mısır Popülasyonlarının Agronomik Performansları

Abstract: Bu araştırmanın ilk yıl sonuçları Ahmet BÜYÜKGÖZ'ün Yüksek Lisans Tezi olarak sunulmuştur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…They found that cob length values were ranged from 17.68 to 22.95 cm. Ozturk and Buyukgoz (2021) were carried out a study to evaluate agronomic performance of some corn landraces in Trabzon. They used 18 corn landraces and two certified corn varieties.…”
Section: Grain Yield and Yield Components Of Cornmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that cob length values were ranged from 17.68 to 22.95 cm. Ozturk and Buyukgoz (2021) were carried out a study to evaluate agronomic performance of some corn landraces in Trabzon. They used 18 corn landraces and two certified corn varieties.…”
Section: Grain Yield and Yield Components Of Cornmentioning
confidence: 99%
“…In Trabzon, a study was performed to determine agronomic performance of some corn landraces. 18 corn landraces and two certified corn varieties were used and cob diameter values varied from 3.34 cm to 4.71 cm (Ozturk and Buyukgoz, 2021). Oktem and Kahramanoglu (2021) were conducted a research on some popcorn genotypes and measured yield and quality parameters.…”
Section: Grain Yield and Yield Components Of Cornmentioning
confidence: 99%